Manual of Benirschke and Kaufmann's Pathology of the Human Placenta - Baergen, Rebecca N. (Springer New York : Imprint: Springer, 2005)
Benirschke and Kaufmann's Pathology of the Human Placenta has long been regarded as the gold standard in the field. It is comprehensive and thorough and contains the detail necessary for those in the subspecialties of placental, perinatal and pediatric pathology. However, placentas are relatively common specimens and are not examined primarily by specialists in the field, but by general pathologists. Thus, there is a need for a more practical and concise manual that can be used by pathology trainees and generalists in their daily work. Manual of Benirschke and Kaufmann's Pathology of the Human Placenta will fill that need. The Manual is a practical, user-friendly guidebook for the general pathologist and pathologist in training for everyday, bench-side use. Organized in 27 chapters, the book will discuss placental development, general features, approach to the specimen by macroscopic and microscopic evaluation, all aspects of placental abnormalities and lesions, disease processes and the placenta, legal aspects of the placental examination, future directions and much more. The sections on macroscopic and microscopic evaluations feature quick-reference tables that allow the reader to identify abnormalities, learn the situations where they occur, and refer back to the text for in-depth discussions. Each chapter will end with selected readings from Pathology of the Human Placenta for more detailed discussions, classic recommended readings, as well as an up-to-date bibliography of current literature. The manual features over 444 illustrations, more than 100 of them in full-color. A must-have for every pathologist and pathology resident.